2015
DOI: 10.1021/jacs.5b07232
|View full text |Cite
|
Sign up to set email alerts
|

Propensity of Hydrated Excess Protons and Hydroxide Anions for the Air–Water Interface

Abstract: Significant effort has been undertaken to better understand the molecular details governing the propensity of ions for the air-water interface. Facilitated by computationally efficient reactive molecular dynamics simulations, new and statistically conclusive molecular-scale results on the affinity of the hydrated excess proton and hydroxide anion for the air-water interface are presented. These simulations capture the dynamic bond breaking and formation processes (charge defect delocalization) that are importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
132
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(157 citation statements)
references
References 53 publications
22
132
0
3
Order By: Relevance
“…However, as will be shown in the next section, the behavior of OH − is completely different al low pH values. On the other hand, the slight decrease of the surface tension of acids with increasing acid concentration suggests that the interaction between H + and the surface is attractive and of the order of 0.5-1 kT, again in agreement with many experimental and computational results [22].…”
Section: Determination Of Short-range Potentials From the Surface Tensupporting
confidence: 88%
“…However, as will be shown in the next section, the behavior of OH − is completely different al low pH values. On the other hand, the slight decrease of the surface tension of acids with increasing acid concentration suggests that the interaction between H + and the surface is attractive and of the order of 0.5-1 kT, again in agreement with many experimental and computational results [22].…”
Section: Determination Of Short-range Potentials From the Surface Tensupporting
confidence: 88%
“…The electrokinetic experiments of both air and oil droplets paint a very similar picture despite having rather disparate chemistries namely, that the zeta potential (ζ) vanishes under acidic conditions and that with increasing pH, it becomes increasingly negative showing that these interfaces retain a negative charge at neutral pH. 3 If waters constituent ions, the proton and hydroxide are the only sources of charging in water, these experiments suggest that the negatively charged OH − ions stick to the surfaces with binding energies on the order of [10][11][12][13][14][15][16][17][18][19][20] times larger than thermal energy 5,6 ! This interpretation has been heavily contested from both experimental and theoretical fronts.…”
Section: Introductionmentioning
confidence: 92%
“…It is found that (H O ) versus [HX] is consistent for distinct halide species within our measurement uncertainty, even if the corresponding /| | appears with different One could convert the deduced K to the partitioning coefficient defined as the ratio of the volume ion density in the surface region to that in the bulk, denoted by KV, if the depth profile of ion distributions can be known. Because such information is not experimentally available, we follow the theoretical reports(4,8,36) to consider the adsorbed hydronium ions to distribute in a surface layer with an effective thickness L that ranges from a H-bonding length (1.97 Å) to an intermolecular distance (~3.1 Å). This approximation yields KV ≈ K/L = 3.61 ~ 5.68, corresponding to a pH difference of the surface with respect to the bulk region,pH, by -0.66 (±0.10), and the adsorption free energy for hydronium ions G = -3.74 (±0.56) kJ/mol.…”
mentioning
confidence: 99%